UPAYA DEWAN KEAMANAN PBB DALAM MELINDUNGI RAKYAT YAMAN PADA REVOLUSI RAKYAT YAMAN TAHUN 2011 - Sutrisna, Indah; Pakpahan, Saiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This research analyzes the implementation of the responsibility to protect the people of Yemen in the civil war by the UN Security Council. Since January 2011, Ali Abdullah Saleh forces have committed systematic and organized crimes against humanity to the protesters causing civilian casualties in large numbers. Crimes against humanity in Yemen shows the inability and unwillingness of the government for implementing the responsibility to protect civilians. This condition shows that yemen government is not capable of running and breaking the concept of Responsibility to Protect. The UN Security Council has the authority in its capacity to take over the responsibility to protect the civilian population of yemen. The role of the Security Council is to implement the concept of Responsibility to Protect on yemen civilians by stating resolution with number 2014 (2011).The responsibility to protect (R to P or R2P) is a norm or set of principles based on the idea that sovereignty is not a privilege, but a responsibility. R to P concept focuses on the three pillars. These are : the responsibility of each individual state to protect its population from genocide, war crimes, ethnic cleansing, and crimes against humanity and their incitement; the responsibility of the international community to undertake peaceful collective action to help states to exercise this responsibility; and the responsibility of the international community to be prepared to take collective action in a timely and decisive manner through the UN Security Council. Any form of a military intervention initiated under the premise of responsibility to protect must fulfill the following six criteria in order to be justified as an extraordinary measure of intervention : just cause, right intention, final resort, legitimate authority, proportional means and reasonable prospect.Keywords : Responsibility to protect, Crimes against humanity, Civil war, United Nation Security Council, United Nation Security Council Resolution.